A new species of Eleocharis (Cyperaceae) from the campos rupestres of northern Minas Gerais, Brazil - Atuesta, Duvier J.; Trevisan, Rafael (Phytotaxa, 2025)
Eleocharis serrae-novae is described and illustrated. This species is known from the Serra Nova e Talhado State Park (Minas Gerais, Brazil), inhabiting open grassland vegetation on sandy substrate. It is morphologically similar to the dwarf members of the genus, especially those with emarginate glumes such as E. angustispicula, E. bahiensis, E. morroi and E. nigrescens, but differs by having inflated sheaths, stramineous spikelets and cancellated achenes. This species is considered Data Deficient (DD) according to the IUCN Red List Categories and Criteria.